2007
DOI: 10.1111/j.1365-2044.2007.05228.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous remifentanil administration on intra‐operative subcutaneous tissue oxygen tension

Abstract: SummarySurgical stress response markedly increases sympathetic nerve activity and catecholamine concentrations. This may contribute to peripheral vasoconstriction, reduced wound perfusion and subsequent tissue hypoxia. Opioids are known to depress the hypothalamic-adrenal response to surgery in a dose-dependent manner. We tested the hypothesis that continuous remifentanil administration produces improved subcutaneous tissue oxygen tension compared to fentanyl bolus administration. Forty-six patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Different pain treatment strategies have also shown to influence P sq O 2 levels significantly. Patients receiving epidural analgesia or a continuous infusion of Remifentanil had higher P sq O 2 during abdominal surgery in comparison to an opioid bolus regiment . Additionally, lower pain scores after elective knee surgeries were correlated with higher P sq O 2 .…”
Section: Discussionmentioning
confidence: 92%
“…Different pain treatment strategies have also shown to influence P sq O 2 levels significantly. Patients receiving epidural analgesia or a continuous infusion of Remifentanil had higher P sq O 2 during abdominal surgery in comparison to an opioid bolus regiment . Additionally, lower pain scores after elective knee surgeries were correlated with higher P sq O 2 .…”
Section: Discussionmentioning
confidence: 92%
“… 24 , 25 The opioid regimen contributes to optimisation of tissue oxygenation by attenuating = vasoconstriction caused by surgical stimulus and adrenergic response. 26 Studies on anaesthetic/opioid interactions have shown that different combinations of effect-site concentrations of propofol and remifentanil are associated with significant differences in arterial blood pressure. 27 , 28 This supports the reliability of arterial blood pressure as a guide to control a strategy toward a definite point of synergy between unconsciousness and analgesia.…”
Section: Discussionmentioning
confidence: 99%